Integrated evidence reveals a new species in the ancient blue coral genus Heliopora (Octocorallia). Issue 1 (December 2018) - Richards, Zoe; Yasuda, Nina; Kikuchi, Taisei; Foster, Taryn; Mitsuyuki, Chika; Stat, Michael; Suyama, Yoshihisa; Wilson, Nerida
Abstract Maintaining the accretion potential and three dimensional structure of coral reefs is a priority but reef-building scleractinian corals are highly threatened and retreating. Hence future reefs are predicted to be dominated by non-constructional taxa. Since the Late Triassic however, other non-scleractinian anthozoans such asHeliopora have contributed to tropical and subtropical reef-building.Heliopora is an ancient and highly conserved reef building octocoral genus within the monospecific Family Helioporidae, represented by a single extant species –H .coerulea, Pallas, 1766. Here we show integrated morphological, genomic and reproductive evidence to substantiate the existence of a second species within the genusHeliopora . Importantly, some individuals of the new species herein described asHeliopora hiberniana sp. nov. feature a white skeleton indicating that the most diagnostic and conservedHeliopora character (the blue skeleton) can be displaced. The new species is currently known only from offshore areas in north Western Australia, which is a part of the world where coral bleaching events have severely impacted the scleractinian community over the last two decades. Field observations indicate individuals of bothH .coerulea andH .hiberniana sp. nov. were intact after the 2016 Scott Reef thermal stress event, and we discuss the possibility that bleaching resistant non-scleractinian reef builders such asHeliopora could provide new ecological opportunities for the reconfiguration of future reefs by filling empty niches and functional roles left open by the regression of scleractinian corals.